Correlation between Molecular Docking Score and Ligand Molar Mass: Statistical Approach - Karnan, R.; Sukumaran, M.; Velavan, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
In recent days, pharmacology researchers have studied secondary metabolic compounds because they are naturally produced by plants, bacteria, fungi, and marine sponges, leading to increased worldwide use of the computational technique of molecular modelling approaches to drug discovery. Flavonoids, which belong to secondary metabolic compounds, play a role in biological activity. In the present study, the flavonoids subclass of secondary metabolic compounds molecular docking binding energy was dependent on the compound's molecular weight on binding interaction with antioxidant proteins using the statistical approaches of correlation coefficient and cluster statistical analysis. To evaluate a strong negative relationship, higher molecular mass flavonoids compounds had high active properties and lower molecular mass flavonoids compounds had low active properties, as reported on antioxidant proteins in correlation (r = -0.76 to -0.91 for a strong relationship) and cluster analysis. Flavonoids subclass compounds molecular docking binding scores were based on ligand molecular mass and depended on a similarly strong negative relationship in molecular mass vs 1HD2, 1MFM, 2F8A, and 2HCK antioxidant proteins. In this study, statistical analysis concluded that molecular docking binding energy depends on ligand molecular mass. Overall, the higher molecular mass compounds have higher active properties may be used in biological activity.